Myeloid antigen-presenting cells in neurodegenerative diseases: a focus on classical and non-classical MHC molecules - Afify, Reham; Lipsius, Katherine; Wyatt-Johnson, Season J.; Brutkiewicz, Randy R. (Frontiers in Neuroscience, 2024)
In recent years, increasing evidence has highlighted the critical role of myeloid cells, specifically those that present antigen (APCs) in health and disease. These shape the progression and development of neurodegenerative disorders, where considerable interplay between the immune system and neurons influences the course of disease pathogenesis. Antigen-presenting myeloid cells display different classes of major histocompatibility complex (MHC) and MHC-like proteins on their surface for presenting various types of antigens to a wide variety of T cells. While most studies focus on the role of myeloid MHC class I and II molecules in health and disease, there is still much that remains unknown about non-polymorphic MHC-like molecules such as CD1d and MR1. Thus, in this review, we will summarize the recent findings regarding the contributions of both classical and non-classical MHC molecules, particularly on myeloid microglial APCs, in neurodegenerative diseases. This will offer a better understanding of altered mechanisms that may pave the way for the development of novel therapeutic strategies targeting immune cell-MHC interactions, to mitigate neurodegeneration and its associated pathology.